Przyroda(i)kultura w epoce antropocenu - Gajewska, Grażyna (Przestrzenie Teorii, 2012)
The article deals with a New Understanding of nature and culture, which is being crystallized in the intellectual current defined by the name of post-humanities. The starting point for the analysis of work of art from the area of bioart – transgenic plant named Edunia, which is a part of a larger project Natural History of the Enigma. Edunia, which does not occur in nature but was created by the artist Eduardo Kac by means of specialists in the field of genetic engineering. A new form of life defined as plantimal shows a DNA expression of the artist included into decorative flowers of petunia. Rose petals of flowers are “interspersed” by dark red vessels the feature of which is the expression of Kac’s gene; this because the artist took care of that that his DNA was found just in the venation of the flower. In the article I present two interpretation paths of this work of bioart which, however, are not a sharp counterpoint to one another, but somewhat differently place accents between nature and culture in their mutual entanglements. One of these paths may be defined as an attempt at making others realise or reminding them about our evolutional species condition, while the other one as an attempt at treating nature as an important actor of the sociopolitical activities.